Modern Analytical Chemistry Meets Heritage Books: Analysis of Volatile Organic Compounds (VOCs) from Two Books Preserved at the Biblioteca Capitolare of Busto Arsizio - Chiara Chiodini; Pierangela Rovellini; Matteo Chiodini; Luca Giacomelli; Daniela Baglio; the 5B IISS Torno Working Group (Molecules)
The development of sensitive, non-invasive methods is essential for the preservation and study of heritage books, allowing insights into their historical production processes and conservation needs. Volatile organic compound (VOC) analysis provides a valuable, non-destructive approach to assess paper composition and degradation in historical volumes. In this study, we analyzed VOC emissions from two books preserved at the Biblioteca Capitolare of Busto Arsizio, Italy: a 16th-century Latin grammar book and a 19th-century mathematics handbook for measurement conversions. Using headspace solid-phase microextraction (HS-SPME) and gas chromatography–mass spectrometry (GC-MS), VOCs were sampled after 24 h of storage at room temperature. The results revealed distinct degradation markers: Straight-chain aldehydes, indicative of lipid oxidation, were more prevalent in the 16th-century book, reflecting the higher quality and durability of its rag-based paper. In contrast, elevated furfural levels in the 19th-century book suggest accelerated cellulose hydrolysis typical of wood pulp paper. Additionally, the presence of menthol and anethole in both volumes points to the use of bacteriostatic agents for preservation. These findings not only highlight differences in material composition but also underscore the importance of tailored conservation approaches for historical documents from different eras.